Feature extraction and classification of Malay speech vowels - Shahrul Azmi Mohd Yusof (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2010)
The main objective of this study is to increase independent speaker Malay vowel recognition capability in terms of accuracy and robustness.